The comparative effects of exercise type on motor function of patients with Parkinson’s disease: A three-arm randomized trial - Li, Fang; Wang, Dongyu; Ba, Xiaohong; Liu, Zhan; Zhang, Meiqi (Frontiers in Human Neuroscience, 2022)
Background Yang-ge dancing is a culturally specific exercise in which people are required to perform motor skills in coordination with rhythmic music. As an integrated exercise with both physical (decelerating the progression of aged-related motor function degeneration) and mental benefits, it has gained great popularity in China, especially among middle-aged and older adults. It remains largely unknown whether Yang-ge dancing (YG) can effectively improve main symptoms of Parkinson’s disease (PD), while conventional exercise rehabilitation program has been recommended in the hospital setting. To this end, this study aimed to investigate the comparative effects of exercise therapy on motor function of PD patients. Materials and methods A sample of 51 PD patients were randomly assigned to Yang-ge dancing, conventional exercise, or conventional exercise with music. Participants in each group performed 60 min per session, five sessions per week of interventions for 4 weeks. All the participants were assessed using the Unified Parkinson’s Disease Rating Scale—motor examination, Berg balance test, timed up and go test, and Purdue pegboard test. Motor performances were examined before and after intervention. Results All the three groups were benefited from exercise. Compared to conventional exercise, the Yang-ge dancing and conventional exercise with music had additional positive effects in mobility with reference to baseline. In addition, compared to the two conventional exercise groups (either with/without music), the Yang-ge dancing further enhanced manual dexterity. Conclusion Exercise with rhythmic auditory stimulation optimized mobility in PD, while YG dance specifically contributed to improvement in manual dexterity. Clinical trial registeration [https://clinicaltrials.gov/], identifier [ChiCTR2200061252].